Integrasi Pendidikan Agama Islam dan Teknologi Informasi: Penanaman Etika Digital Siswa Sekolah Dasar Menuju Generasi Berkarakter di Era Society 5.0 - Frafasta Yafithufail; Mas’ady Ashabul Kahfi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The Society 5.0 era demands the integration of digital literacy and religious character formation at the elementary school level. This study aims to analyze the role and model of integrating Islamic Religious Education (PAI) and Information and Communication Technology (ICT) in cultivating students’ digital ethics. Using a qualitative case study method at SDN Ngablak 1 Kediri, data were collected through interviews, observation, and documentation. The findings indicate that Islamic values such as trustworthiness (amanah), responsibility, and digital etiquette significantly shape students’ ethical awareness in using technology. The integration of PAI–ICT was implemented through digital project-based learning, teacher role modeling, and school–parent collaboration in monitoring students’ digital behavior. Conceptually, this synergy represents an adaptive Islamic education model that harmonizes technological advancement with moral values. The integrated PAI–ICT approach contributes to developing a digitally literate yet ethical and character-driven generation in the Society 5.0 era.